2022
DOI: 10.1002/advs.202106063
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Single‐Cell Analyses Outline the Immune Microenvironment and Therapeutic Effectors of Interstitial Cystitis/Bladder Pain Syndrome

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) has a significant impact on quality of life, but the etiopathogenesis remains largely unknown. The bladder microenvironment of patients with IC/BPS to obtain biological evidence supporting diagnosis and novel therapy is systematically characterized. Single-cell RNA sequencing (scRNA-seq) and image mass cytometry (IMC) are applied to bladder biopsies of the IC/BPS cohort. A total of 42 distinct cell clusters are identified from different groups. The increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…IC/BPS patients have altered urothelial cell expression of proinflammatory cytokines and chemokines, including IL1b, and TNFa (14,43), while urine samples from IC/BPS patients contain elevated levels of IL1b, IL8, CXCL1, CXCL10 (44)(45)(46)(47), possibly derived from urothelial cells, as observed in our study, where significantly higher concentration of these cytokines and chemokines was determined in TNFa-stimulated cells. Abnormalities in specific proinflammatory signaling networks that contribute to alterations in bladder immune and structural cell phenotypes were recently uncovered by Su et al (40), who performed single cell RNA seq in bladder tissues of patients with IC/BPS. They have also shown that immune response during IC/BPS is characterized by extensive infiltration of TNFa-producing neutrophil granulocytes and macrophages in bladder tissue (40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IC/BPS patients have altered urothelial cell expression of proinflammatory cytokines and chemokines, including IL1b, and TNFa (14,43), while urine samples from IC/BPS patients contain elevated levels of IL1b, IL8, CXCL1, CXCL10 (44)(45)(46)(47), possibly derived from urothelial cells, as observed in our study, where significantly higher concentration of these cytokines and chemokines was determined in TNFa-stimulated cells. Abnormalities in specific proinflammatory signaling networks that contribute to alterations in bladder immune and structural cell phenotypes were recently uncovered by Su et al (40), who performed single cell RNA seq in bladder tissues of patients with IC/BPS. They have also shown that immune response during IC/BPS is characterized by extensive infiltration of TNFa-producing neutrophil granulocytes and macrophages in bladder tissue (40).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in specific proinflammatory signaling networks that contribute to alterations in bladder immune and structural cell phenotypes were recently uncovered by Su et al (40), who performed single cell RNA seq in bladder tissues of patients with IC/BPS. They have also shown that immune response during IC/BPS is characterized by extensive infiltration of TNFa-producing neutrophil granulocytes and macrophages in bladder tissue (40). Their observations go hand in hand with our findings suggesting an active role of urothelial cells in shaping the bladder immunity through altered proinflammatory cytokine and…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MacSpectrum and AtheroSpectrum have been published both as free web tools and as R packages (https://macspectrum.uconn.edu), and they have since been used to further evaluate macrophages in a number of disease conditions, including obesity, 79,80 diabetes, 81 pulmonary fibrosis, 82 liver disease, 83,84 cancer, 85,86 and interstitial cystitis 87 in addition to our own work on CVD 58 and adipose tissue thermogenesis. 88 In the future, we hope that these tools are applied to characterize macrophage functions in additional pathologies.…”
Section: Discussionmentioning
confidence: 99%